Analysis of Short Latencies In Industrial Network Environments - Morawski, Michał (Journal of Applied Computer Science, 2006)
The bibliography shows the typical shape of probability density function (PDF) that describe network latencies. The paper presents the results of the measurements of the PDF of Round Trip Time (RTT) in real network environments. The results show, that the appropriate PDFs are significantly differentiated and depend on the kind of the network, its load, peers load, logic of applications, etc. The PDF measurments is focused on industrial network control programs transmissions, where only loses and short delays are important.